(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the effectiveness of using interactive pedagogical methods in economic education of primary school pupils. During the study, interactive techniques such as brainstorming, clustering, role-playing, and situational tasks were implemented in classroom lessons to explore their impact on pupils’ economic thinking skills, frugality and responsibility, and overall financial literacy. The findings show that use of interactive methods significantly increases students’ engagement during lessons, and helps in fostering independent and conscious decision-making skills necessary for managing economic resources and handling real-life financial situations.